A Novel Finding: Macrophages Involved in Inflammation Participate in Acute Aortic Dissection Complicated with Acute Lung Injury - Wu, Z.; Wang, Z.; Xu, P.; Zhang, M.; Cheng, L.; Gong, B. (Current Molecular Medicine, 2017)
Background: Little is known about the pathogenesis of acute lung injury (ALI) complicated with acute aortic dissection (AAD). Objective: We aim to investigate the roles of macrophages-derived matrix metalloproteinase 9 (MMP9) in the development of ALI complicated with AAD and factors involved in the recruitment of macrophages. Methods: This study included three parts: (i) Determination of serum MMPs, angiotensin II (AngII) and MCP-1 in patients with AAD complicated with ALI or AAD only, non-ruptured chronic aortic aneurysm patients or healthy volunteers using ELISA method. (ii) A novel AAD complicated with ALI model was established by infusing angiotensin II (AngII) to immature rats treated with β-aminopropionitrile monofumarate (BAPN) to identify the potential roles of MMP9 and MCP-1 in AAD complicated with ALI. (iii) Cultured pulmonary microvascular endothelial cell (PMVEC) line was used to investigate how AngII was involved in the release of MCP-1 in rat pulmonary vascular endothelial cells. Results: Serum MMP9, AngII and MCP-1 were remarkably elevated in patients with AAD complicated with ALI. The MMP9 expressed in pulmonary tissues was derived from macrophages. In the animal model, the release of MMP9 from macrophages finally resulted in ALI, while inhibition of MMP9 and MCP-1 contributed to decreased incidence of AAD complicated with ALI. In vitro experiments indicated that AngII triggered overexpression of MCP-1 in PMVECs by activating NF-ΚB signaling pathway. Conclusion: AAD complicated with ALI is highly associated with the macrophages infiltrating the pulmonary interstitial tissue and released MMP9 in response to angiotensin II. MCP-1 is closely related to the recruitment of macrophages.
Keywords: angiotensin II